Design of Spot Welding Robot - Zelun Li; Zhicheng Huang; Youjun Huang (Institute of Advanced Engineering and Science, 2013)
Welding robot has played an extremely important role in the welding production of high-quality, high-efficiency. The paper designed the hardware structure and software of spot welding robot. The hardware design mainly includes the major modules of arm and base; the hardware design includes two parts: manual mode and automatic mode. Manual mode is generally used for the robot system installation, commissioning and troubleshooting, and the major modules are controlled by the start of the corresponding button; automatic mode is mainly used for production stage. The welding robot uses PLC for controlling; the system runs faster and has a short production cycle. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.2899